Free government in the making : - Mason, Alpheus Thomas (Oxford University Press, 1949)
Contents: The doer, the so-called practical man, has ever been pre-eminent in American culture. The pioneering man of action cleared the forrest, conquered the foe, and established the foundations of political independence...